Insights into the prey of Vespa mandarinia (Hymenoptera: Vespidae) in Washington state, obtained from metabarcoding of larval feces - Wilson, Telissa; Looney, Chris; Tembrock, Luke R.; Dickerson, Sapphitah; Orr, Jessica; Gilligan, Todd M.; Wildung, Mark (Frontiers in Insect Science, 2023)
The northern giant hornet, Vespa mandarinia (Hymenoptera: Vespidae), was detected for the first time in North America in 2019. Four nests have since been located and removed in northwestern Washington State as part of an extensive survey and eradication program. This recent introduction into North America has prompted new research on the biology and ecology of V. mandarinia to help inform management strategies. In its native range, V. mandarinia is known to prey on a variety of insects including the economically important honey bee species Apis cerana and Apis mellifera. Although A. cerana has developed defense mechanisms against attack by V. mandarinia, A. mellifera have no such defenses and an entire hive can be quickly destroyed by only a few hornets. In North America the hornet has been observed foraging on paper wasps (Polistes dominula) and honey bees, but little else is known about prey use in its novel range. To address this knowledge gap, we employed a DNA metabarcoding approach to characterize species detected in larval feces collected from all Washington V. mandarinia nests found to date. Sequences were recovered for 56 species across fourteen orders. The most frequently detected species were other social Hymenoptera, with Dolichovespula maculata, P. dominula, and A. mellifera present in most samples. All of the species detected, except for A. mellifera, represent new prey records for V. mandarinia, with eight families of insects newly associated with giant hornets. These results suggest that V. mandarinia in Washington preys on an assortment of insects similar to those documented in its native range, and that this new invader has readily incorporated novel species into its foraging and diet.